Description of three new species of Myrmeleon Linnaeus, 1767 from West Africa (Neuroptera: Myrmeleontidae) - Michel, Bruno; Akoudjin, Massouroudini (Zootaxa, 2023)
Three antlion species, Myrmeleon croceus n. sp., Myrmeleon foucarti n. sp. and Myrmeleon nemoleontoides n. sp. from West Africa are described and illustrated. Information on their distribution, ecology and predators is provided.